Attitudes of sport parents towards children's eating habits - YAMAN, ÇETİN (My University, 2024)
Today, parents have assumed important roles in shaping their children\"s eating habits in social and daily life. Especially the tendency of parents who do sports to transfer their healthy lifestyles to their children has positive effects on children\"s eating habits. This study examines the attitudes of parents on this issue and the effects of these attitudes on children\"s eating habits. In line with the aim of the study, the attitudes of parents who do sports towards their children\"s eating habits were investigated. The rationale of the study is to focus on how parents\" attitudes towards nutrition affect their children\"s eating habits and the contribution of these attitudes to children\"s general health and sports performance. The findings of the study show that parents\" nutrition attitudes are critical for children to develop a healthy lifestyle. This study was conducted between 2023-2024 and 860 parents and their children participated in the study. The data obtained from the study were collected using a 5-point Likert-type scale form with validity and reliability and analysed with SPSS 22.0 software. Various statistical techniques such as descriptive statistics, reliability analysis, independent sample t-test, ANOVA, factor and regression analyses were used in the study. The findings obtained at the end of the research show that parents\" nutritional attitudes have significant effects on children\"s eating habits. Parents\" attitudes towards healthy eating and physical activity positively affect children\"s eating habits. Children of parents who do sports develop healthier eating habits, are more active and take part in physical activities. The study reveals that parents\" nutritional attitudes contribute to children\"s general health and sports performance.

Hoy en día, los padres han asumido un papel importante en la formación de los hábitos alimentarios de sus hijos en la vida social y cotidiana. Especialmente la tendencia de los padres que practican deporte a transferir sus estilos de vida saludables a sus hijos tiene efectos positivos en los hábitos alimentarios de éstos. Este estudio examina las actitudes de los padres sobre este tema y los efectos de estas actitudes en los hábitos alimentarios de los niños. De acuerdo con el objetivo del estudio, se investigaron las actitudes de los padres que hacen deporte hacia los hábitos alimentarios de sus hijos. La razón de ser del estudio es centrarse en cómo afectan las actitudes de los padres hacia la nutrición a los hábitos alimentarios de sus hijos y la contribución de estas actitudes a la salud general y al rendimiento deportivo de los niños. Los resultados del estudio muestran que las actitudes de los padres hacia la nutrición son fundamentales para que los niños desarrollen un estilo de vida saludable. Este estudio se llevó a cabo entre 2023-2024 y en él participaron 860 padres y sus hijos. Los datos obtenidos en el estudio se recogieron utilizando un formulario de escala tipo Likert de 5 puntos con validez y fiabilidad y se analizaron con el programa informático SPSS 22.0. En el estudio se utilizaron diversas técnicas estadísticas, como estadística descriptiva, análisis de fiabilidad, prueba t de muestras independientes, ANOVA, análisis factorial y de regresión. Los resultados obtenidos al final de la investigación muestran que las actitudes nutricionales de los padres tienen efectos significativos en los hábitos alimentarios de los niños. Las actitudes de los padres hacia una alimentación sana y la actividad física afectan positivamente a los hábitos alimentarios de los niños. Los hijos de padres que hacen deporte desarrollan hábitos alimentarios más saludables, son más activos y participan en actividades físicas. El estudio revela que las actitudes nutricionales de los padres contribuyen a la salud general y al rendimiento deportivo de los hijos. Palabras clave: padres; niños; nutrición; salud; deporte.
Actitudes de los padres deportistas ante los hábitos alimentarios de sus hijos
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Rehabilitasyon; Clinical Medicine (Med); Clinical Medicine; Rehabilitation; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; children; health; nutrition; parents; sport; padres; niños; nutrición; salud; deporte